Can cannibalizing cancer cells challenge classic cell death classification? - Walton, Emma Louise (Biomed J, 2017)
In this issue of the Biomedical Journal, we learn about a novel are still largely mysterious mechanism of cell death that is challenging classification systems of cell death pathways and could have important implications for future cancer therapy. We also learn of a promising biomarker to stratify patients into risk groups after stroke. Finally, this issue also includes two studies investigating factors that influence outcome after heart surgery.